Choosing Wisely: Persistent Amylase Concurrent With Lipase Testing at Multiple Academic Health Systems. (11th September 2019) - Ritter, Jacob; Ghirimoldi, Federico; Manuel, Laura; Moffett, Eric; Shireman, Paula; Brimhall, Bradley
Abstract: Objectives: Choosing Wisely is a multidisciplinary effort to reduce unnecessary tests and procedures. Evidence-based guidelines advocate using serum lipase to diagnose acute pancreatitis; concurrent amylase and lipase tests provide minimal benefit compared to either alone. Serial measurements after the first elevated test are ineffective for tracking disease course. Our study determined the number of concurrent amylase/lipase tests and unnecessary serial tests to examine adherence to Choosing Wisely recommendations at four academic health systems. We also identified provider-ordering patterns and quantified the variable and total costs of unnecessary tests. Methods: We analyzed deidentified laboratory data from four academic health systems in the Greater Plains Collaborative for all serum amylase and lipase tests from 2017, including results, timing, and patient-encounter location. We defined concurrent tests occurring within a 24-hour period and unnecessary serial inpatient measurements occurring after the first elevated result. Conclusion: While the majority of providers adhered to Choosing Wisely recommendations obtaining 58, 693 lipase-only tests, 85.8% of amylase tests were obtained in parallel with lipase (20, 771 concurrent tests; amylase only, 3, 447; total amylase tests, 24, 218). Encounter location revealed concurrent rates of 43%, 32%, and 5% for ambulatory, inpatient, and emergency department settings, respectively. Ambulatory clinics from multiple services obtained concurrent tests, with Family Medicine obtaining 48%. Services with order sets containing both amylase and lipase were associated with higher rates of concurrent testing. Inpatient unnecessary serial testing resulted in 413 amylase and 1, 266 lipase tests occurring in 33% and 31% of inpatient encounters for amylase and lipase, respectively. Unnecessary amylase and lipase tests resulted in 31, 195 variable costs and in 86, 297 total costs. Targeted education to clinicians/services ordering unnecessary amylase/lipase tests and revising order sets could decrease costs and improve quality of care by decreasing the volume and frequency of blood draws. Funded by UL1TR002645 and the Greater Plains Collaborative.